2004
DOI: 10.1093/annonc/mdh189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cervical spinal cord stimulation on regional blood flow and oxygenation in advanced head and neck tumours

Abstract: Cervical-SCS increased tumour oxygenation and CCA blood flow, and could enhance the loco-regional delivery of oxygen, radiosensitising and chemotherapeutic drugs. Cervical-SCS as adjuvant in chemoradiotherapy of these tumours warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
1
16
0
4
Order By: Relevance
“…Clavo and colleagues [56][57][58][59][60] explored a potential novel application of SCS, investigating the effects of cervical SCS on CBF in patients with high-grade gliomas and head and neck tumors. These malignancies have a decreased locoregional blood flow resulting in reduced delivery of chemotherapy and oxygen, as well as an increase in radiation resistance to radiotherapy, and represent an important adverse prognostic factor.…”
Section: Clinical Trials On Hypoperfusion Syndromes In Humansmentioning
confidence: 99%
“…Clavo and colleagues [56][57][58][59][60] explored a potential novel application of SCS, investigating the effects of cervical SCS on CBF in patients with high-grade gliomas and head and neck tumors. These malignancies have a decreased locoregional blood flow resulting in reduced delivery of chemotherapy and oxygen, as well as an increase in radiation resistance to radiotherapy, and represent an important adverse prognostic factor.…”
Section: Clinical Trials On Hypoperfusion Syndromes In Humansmentioning
confidence: 99%
“…SCS has been shown to augment CBF and speculated to protect the brain from focal ischemia in a large series of experiments, both on animals and on humans [47,48,49,50,51,52,53], and has been proposed for the treatment of several cerebral low-perfusion syndromes [54,55,56,57,58,59,60,61,62,63,64,65,66,67]. However, there is not yet an ultimate scientific explanation; moreover, a clear understanding of the mechanisms elicited by SCS is still lacking [4,53,68].…”
Section: Discussionmentioning
confidence: 99%
“…We have not, as yet, established the optimum stimulation schedule to obtain a maximal effect in tumor blood flow, or oxygenation. Our previous experiences with contact-thermography technique in non-cancer patients 24 and in two H&N cancer patients 5 showed that up to an hour of stimulation may be necessary to obtain the maximal effect in these tissues. Further studies are needed to optimize the this effect and the impact of cSCS on the survival of patients with brain tumors needs be evaluated.…”
Section: Discussionmentioning
confidence: 99%